Naprężenia Termiczne w Półprzestrzeni Sprężystej Wywołane Ruchomym Źródłem Ciepła - J. Kubik (Engineering Transactions, 1974)
The paper presents the thermal and mechanical effects of a moving, linear heat source in an elastic halfspace; the source propagates at a constant velocity v in the direction perpendicular to the surface of the halfspace. The surface is assumed to be held at zero temperature and free of kinematic constraints. The conditions of plane strain are satisfied. The temperature field is constructed by superposing two heat sources, a positive and a negative one, acting within an elastic space. Thermoelastic strain potential and Galerkin functions are used in the solution. The results are illustrated by a numerical example and several graphs.